2005
DOI: 10.1186/1471-2458-5-122
|View full text |Cite
|
Sign up to set email alerts
|

Patient and health service delay in pulmonary tuberculosis patients attending a referral hospital: a cross-sectional study

Abstract: Background: Delays in diagnosis and initiation of effective treatment increase morbidity and mortality from tuberculosis as well as the risk of transmission in the community. The aim of this study was to determine the time taken for patients later confirmed as having TB to present with symptoms to the first health provider (patient delay) and the time taken between the first health care visit and initiation of tuberculosis treatment (health service delay). Factors relating to these 'delays' were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
122
12
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 4 publications
23
122
12
4
Order By: Relevance
“…This may be due to stigma; patients who suspect TB may be afraid to consult a care provider while those who think that they are free of TB more confidently access care [26]. Patients who had history of COPD also delayed significantly more than those with a negative history [26]. This may be because patients with a history of COPD assume that their symptoms are due to COPD and hence they do not seek help.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This may be due to stigma; patients who suspect TB may be afraid to consult a care provider while those who think that they are free of TB more confidently access care [26]. Patients who had history of COPD also delayed significantly more than those with a negative history [26]. This may be because patients with a history of COPD assume that their symptoms are due to COPD and hence they do not seek help.…”
Section: Discussionmentioning
confidence: 78%
“…Patients who suspected TB tended to delay more than those who did not. This may be due to stigma; patients who suspect TB may be afraid to consult a care provider while those who think that they are free of TB more confidently access care [26]. Patients who had history of COPD also delayed significantly more than those with a negative history [26].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Patient delay was more among alcohol users in other studies by Tobgay KJ et al at Sikkim, and Kiwuwa MS et al at Uganda. 12,33 It is possible as cough itself is a common, non-specific symptom which may more likely be attributed to common conditions such as asthma, sinusitis or postnasal drip by patients. This leads to delayed care seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple visits influence healthsystem delays in several ways: receiving inappropriate antibiotic treatment, for example, can worsen or otherwise modify the clinical picture; patients might believe that they will be cured; and in the long term, patients or their family members may choose alternative services [25]. Others have also found that repeated visits cause delays if they do not lead to the correct diagnosis [20,26]. There is no clear line of demarcation between private and public HCPs, and either private HCPs or public HCPs may be consulted subsequently; improving the quality of both private and public health services could help reduce the delays [25].…”
Section: Factors Associated With Patient Delaysmentioning
confidence: 99%